Drought and air warming affects abundance and exoenzyme profiles of Cenococcum geophilum associated with Quercus robur, Q. petraea and Q. pubescens. (11th June 2012) - Herzog, C.; Peter, M.; Pritsch, K.; Günthardt‐Goerg, M. S.; Egli, S.
Abstract: The present study aimed to elucidate the influence of drought and elevated temperature on relative abundance and functioning of the ectomycorrhizal fungus Cenococcum geophilum on three oak species differing in adaptation to a warm and dry climate. The experiment QUERCO comprised three Quercus species ( Q. robur, Q. petraea, Q. pubescens ) grown for 3 years under four treatments: elevated air temperature, drought, a combination of the two, and control. Fine root samples were analysed for relative abundance and potential extracellular enzyme activities of ectomycorrhizae of C. geophilum, a fungal species known to be drought resistant. The relative abundance of C. geophilum on the roots of the oak species was significantly increased by temperature, decreased by drought, but unchanged in the combined treatment compared to the control. Although the extent of treatment effects differed among oak species, no significant influence of tree species on relative abundance of C. geophilum was detected. Exoenzyme activities of C. geophilum on Q. robur and Q. petraea (but not Q. pubescens ) significantly increased in the combined treatment, but for all oak species were reduced under drought and air warming alone compared to the control. There was a significant negative correlation between abundance of C. geophilum and its leucine aminopeptidase activity. As this enzyme is not frequent among ectomycorrhizal fungi, this emphasises the functional importance of C. geophilum in the ectomycorrhizal community. Our results indicate that increased temperature and drought will influence the relative abundance and enzyme activity of C. geophilum. However, both the Quercus species and C. geophilum tolerated warming and strong drought.